Pengolahan Limbah Cair Industri Tahu Menggunakan Tanaman Typha Latifolia Dengan Metode Constructed Wetland - Muhammad Azmi; Edward HS; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tofu industry is a domestic industry largely do not have sewage treatment units, wherewastewater directly discharge into sewers or water bodies without treatment. The aims ofstudy observation the ability of constructed wetland using T. latifolia to removal, COD andTSS. The research variations were plant and detention time. Constructed wetland reactorusing plastics with dimension 50, 36, 31cm, in length x width x height and soil mediathickness of 10 cm, 5 cm sand and 5 cm gravel. T. latifolia plant density 0, 0,5, 0,75 and 1g/cm2, and variations detention time 1,2, and 3 day. Optimal results were obtained in plantsTypha latifolia 1 g/cm2 and detention time day to 3 there are COD 200 mg/L and efficiency of92,70%; TSS 153 mg/L with efficiency 87,90%;. Anova analysis results α = 5% show thevalue COD 98,8%; and TSS 92,8%. Wich explains that the plant density factor and detentiontime affect the the concentration reduction COD and TSS.Keywords: Thypa latifolia, Constructed wetland, Detention time, Wastewater tofu.